Batwoman : elegy - Rucka, Greg (DC Comics, 2010)
Kate Kane transforms herself into Batwoman and battles a madwoman who calls herself Alice, after the character Alice in Wonderland, and thinks that everyone in Gotham is expendable in the fairy tale she has created.